2021
DOI: 10.1002/ppul.25462
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in children with cystic fibrosis: More under the covers

Abstract: Cystic fibrosis (CF) is a chronic multisystem disease with manifestations from birth. It involves the entire respiratory system, with increased cough, and recurrent pulmonary infections, and it also leads to intestinal malabsorption, all of which can have an impact on sleep. In this review, we summarize the available literature on the various sleep disturbances in children with CF. Sleep quality and sleep efficiency are often impaired in children with CF. They may be accompanied by symptoms associated with sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
4
1
0
Order By: Relevance
“…However, sleep architecture (N1, N2, N3 and REM stages) was preserved despite reduced sleep quality. These findings are consistent with data from other studies in children and adult pwCF [ 13 , 19 , 23 , 53 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, sleep architecture (N1, N2, N3 and REM stages) was preserved despite reduced sleep quality. These findings are consistent with data from other studies in children and adult pwCF [ 13 , 19 , 23 , 53 ].…”
Section: Discussionsupporting
confidence: 93%
“…Most current data regarding sleep quality and sleep architecture in pwCF come from studies in children and adolescents. Consistent with existing literature in adult pwCF [ 22 , 24 , 52 , 53 ], we confirmed that these patients have reduced sleep quality (total sleep time, sleep efficiency) and increased sleep latency and wake after sleep onset. There are multiple potential contributors to impaired subjective and objective sleep in pwCF, including nocturnal coughing, pain, chronic rhinosinusitis, CF-related diabetes, and PEG-feeding [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that despite reduced sleep quality, sleep architecture (N1, N2, N3 [slow-wave sleep], and REM stages) is preserved. This is consistent with the results of other studies in children and adult pwCF [7, 22, 46, 47].…”
Section: Discussionsupporting
confidence: 93%
“…PwCF often report disturbed sleep. Nocturnal coughing, chronic rhinosinusitis and nasal polyps, hypoxia, and increased work of breathing negatively affect sleep and lead to abnormal sleep with significantly reduced TST and SE, and increased SL and WASO [21,[44][45][46]. These results are confirmed by the current study, which showed reduced sleep quality in adult pwCF.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, different from patients with bronchiectasis and mycobacterial infections, patients with CF often manifest poor sleep quality with frequent awakenings and daytime sleepiness, and such disturbances are more frequent with the progression of the disease [ 68 ]. Despite this, SDB prevalence is still under-recognized in this population of patients and may impact disease outcomes [ 69 ].…”
Section: Sleep-disordered Breathing and Cystic Fibrosismentioning
confidence: 99%